Execution of dependent rights objects due to overlapping land for the purpose of debt repayment : (Case Study of Supreme Court Decision Number: 25 PK / TUN / 2021) - Erizka Shavirra Rachael; Edith Ratna Mulyaningrum (LEGAL BRIEF, 2022)
This research analyzes the execution of dependent rights objects due to overlapping land for the purposes of debt repayment (case study of supreme court decision number: 25 pk / tun / 2021), The method used is normative legal research that is descriptive, analyzing secondary data in the form of primary legal materials and secondary legal materials. Data acquisition using literature study techniques and analyzed in a qualitative way draws conclusions with deductive logic. This study discusses the arrangement of the execution of collateral objects due to overlapping land for debt repayment based on laws and regulations related to legal remedies from the failure of execution of collateral objects due to overlapping land for debt repayment purposes, How are the implications of the execution of collateral objects due to overlapping land for debt repayment costs based on Supreme Court Decision Number:  25 PK/TUN/2021.